Myocardial protection by ischemic remote conditioning in coronary revascularization - Rudy Hernández Ortega; Maria Oslaida Agüero Martínez; Osvaldo González Alfonso; María Idoris Cordero Escobar; Teddy Osmín Tamargo Barbeito (Revista Cubana de Anestesiología y Reanimación, 2019)
Introduction: A series of short periods of distant ischemia, prior to the major ischemic event, can limit the myocardial damage produced by ischemia or reperfusion. Objective: To evaluate the usefulness of remote ischemic conditioning in patients scheduled for surgical procedures of coronary revascularization. Methods: A quasi-experimental, explanatory, comparative study with historical control was conducted in two groups of 247 patients proposed for coronary revascularization. A tourniquet was placed in the right arm in the study group, alternating 3 insufflations with 3 dessufflations with a pressure of 200 mmHg, keeping each for 5 minutes. This procedure was performed before, during and after the major ischemic event, caused by the impingement of the coronary artery. Results: A significant decrease in enzymatic parameters was achieved. No significant differences were found (p> 0.05) according to a set of variables that represent the initial state of the patients.